2021
DOI: 10.1016/j.msard.2020.102673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozanimod on Symbol Digit Modalities Test Performance in Relapsing MS

Abstract: Background: Cognitive dysfunction, including slowed cognitive processing speed (CPS), is one of the most disabling symptoms of multiple sclerosis (MS). The Symbol Digit Modalities Test (SDMT) is a preferred measure of CPS for MS trials and routine screening. Based on encouraging SDMT results in the phase 3 SUNBEAM trial, these post hoc, exploratory analyses were conducted to further compare effects of the sphingosine 1-phosphate receptor modulator ozanimod versus intramuscular interferon β-1a on CPS in partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
(52 reference statements)
0
21
0
1
Order By: Relevance
“…In SUNBEAM (NCT02294058), a phase III RCT in RMS, mean change in SDMT Z-score over 1 year was greater for ozanimod-groups (0.5 mg: n = 450; 1.0 mg: n = 447) compared with interferon beta-1a group (n = 448) (mean difference from baseline to month 12 vs interferon β 1a: ozanimod 0.5 mg = 0.082 [95% CI = 0.010;0.153], p = 0.02; ozanimod 1.0 mg = 0.111 [95% CI = 0.039;0.182], p = 0.002) [12]. This was further confirmed in a post hoc analysis of the same RCT [14], which also showed that the 1.0 mg ozanimod-group (n = 444) had a significantly greater proportion of RMS showing ≥ 4-point SDMT improvement at month 6 (30.0% vs. 22.2%, rate ratio = 1.3 [95% CI = 1.08;1.68], p = 0.008) and month 12 (35.6% vs. 27.9%, rate ratio = 1.2 [95% CI = 1.02;1.50], p = 0.03) compared with interferon β 1a-group (n = 446) [14].…”
Section: Dmt Effects On Cognitive Functions: What Is New?mentioning
confidence: 68%
See 1 more Smart Citation
“…In SUNBEAM (NCT02294058), a phase III RCT in RMS, mean change in SDMT Z-score over 1 year was greater for ozanimod-groups (0.5 mg: n = 450; 1.0 mg: n = 447) compared with interferon beta-1a group (n = 448) (mean difference from baseline to month 12 vs interferon β 1a: ozanimod 0.5 mg = 0.082 [95% CI = 0.010;0.153], p = 0.02; ozanimod 1.0 mg = 0.111 [95% CI = 0.039;0.182], p = 0.002) [12]. This was further confirmed in a post hoc analysis of the same RCT [14], which also showed that the 1.0 mg ozanimod-group (n = 444) had a significantly greater proportion of RMS showing ≥ 4-point SDMT improvement at month 6 (30.0% vs. 22.2%, rate ratio = 1.3 [95% CI = 1.08;1.68], p = 0.008) and month 12 (35.6% vs. 27.9%, rate ratio = 1.2 [95% CI = 1.02;1.50], p = 0.03) compared with interferon β 1a-group (n = 446) [14].…”
Section: Dmt Effects On Cognitive Functions: What Is New?mentioning
confidence: 68%
“…Emerging data also support the beneficial effects on cognitive functions of siponimod [8] and ozanimod [12,14], two selective modulators of sphingosine 1 phosphate receptors, which have been recently approved for secondary progressive (SP) MS and RMS, respectively.…”
Section: Dmt Effects On Cognitive Functions: What Is New?mentioning
confidence: 86%
“…The efficacy outcome measures of the OzEAN study complement those of the phase 2 and 3 clinical trials ( Table 5 ), which focused on traditional, physician-reported assessments of relapses (ARR) and disability progression (EDSS), MRI parameters (gadolinium-enhancing lesions, T2 lesions, and brain atrophy), and functional measures [the Multiple Sclerosis Functional Composite (MSFC)( 33 )), which comprises the Timed 25-Foot Walk (lower limb function and walking speed), Nine-Hole Peg Test (upper limb function and dexterity), and either the SDMT or the Paced Auditory Serial Addition Test (cognition) ( 4 , 6 , 7 , 34 , 35 ). QoL was assessed in the phase 3 studies using the MSQOL-54, but no other PROs were employed ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the field researchers are well aware of the practice effects challenges, it is concerning that the studies aimed to assess the effects of DMTs on cognitive evolution have systematically overlooked the practice effects in interpreting their results. For example, the SDMT practice effect is wholly disregarded in the OPERA and the SUNBEAM studies ( 3 , 6 ). Furthermore, these studies expedite and amplify the learning effects by using short and frequent retesting intervals (at 12-week intervals in the OPERA study ( 3 ) and 6-month intervals in the EXPAND ( 5 ) and SUNBEAM ( 6 ) studies), which contribute to exacerbating the improved SDMT performance.…”
Section: Discussionmentioning
confidence: 99%